PRELIMINARY OBSERVATION ON NESTING ECOLOGY OF ENDANGERED BROWN-CHEEKED BULBUL (ALOPHOIXUS BRES) IN JATIMULYO AGROFORESTRY - Agus Nurrofik; Adityas Arifianto; Afina Aninnas; Kelik Suparno; Agung S. Kurnianto; Luhur Septiadi; Nia Kurniawan (BRIN Publishing (Penerbit BRIN), 2023)
We found an active nest of endangered Brown-cheeked Bulbul (Alophoixus bres) with two chicks in nest-adoption program at Jatimulyo village, Yogyakarta province, Indonesia on 19 December 2021. It was placed on the lateral branch of apus bamboo (Gigantochloa apus) 1.5 m high. The nest was cup-shaped, with outer diameter of ± 8 cm, inner diameter of ± 6 cm, and depth of ± 3 cm. It was made of living non-vascular plants and plant fragments. Our observation revealed that the food of the chicks was primarily comprised of insects (in the morning) and fruits (at midday). The insect preys include caterpillars, Lepidoptera, Coleoptera, Orthoptera and Diptera. The fruits were mangir, lempeni, and senggani